2016
DOI: 10.1088/0957-4484/27/44/445710
|View full text |Cite
|
Sign up to set email alerts
|

Supercollision cooling effects on the hot photoluminescence emission of graphene

Abstract: We report on hot photoluminescence measurements that show the effects of acoustic phonon supercollision processes in the intensity of graphene light emission. We use a simple optical method to induce defects on single layer graphene in a controlled manner to study in detail the light emission dependence on the sample defect density. It is now well accepted that the graphene photoluminescence is due to black-body thermal emission from the quasi-equilibrium electrons at a temperature well above the lattice tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…In the second case, the possibility of the fast photocarrier relaxation originated from defects in the graphene is examined. Early studies have shown that photocarrier relaxation is accelerated by supercollision cooling process, i.e., carrier–phonon scattering with acoustic phonons through a defect state in graphene. , However, the weak D band in the Raman spectra in Figure a indicates that the number of defects in the epGr samples used in this study is small, and the defect-mediated relaxation cannot be as fast as the observed PL decay (details are given in the SI), , thus, the second possibility is rejected. In the third case, the possibility for fast photocarrier relaxation due to phonons of the substrate is discussed.…”
Section: Resultsmentioning
confidence: 90%
“…In the second case, the possibility of the fast photocarrier relaxation originated from defects in the graphene is examined. Early studies have shown that photocarrier relaxation is accelerated by supercollision cooling process, i.e., carrier–phonon scattering with acoustic phonons through a defect state in graphene. , However, the weak D band in the Raman spectra in Figure a indicates that the number of defects in the epGr samples used in this study is small, and the defect-mediated relaxation cannot be as fast as the observed PL decay (details are given in the SI), , thus, the second possibility is rejected. In the third case, the possibility for fast photocarrier relaxation due to phonons of the substrate is discussed.…”
Section: Resultsmentioning
confidence: 90%
“…The PL spectra show a broad wavelength light emission, figure 2(d). After excitation by a pulsed laser, the photoexcited electrons and holes thermalize through carrier-carrier scattering on a time scale of tens of femtoseconds and a quasi-equilibrium distribution of hot-electrons is formed with an effective temperature higher than the lattice temperature and these hot electrons can emit light as a thermal black body like radiation, with a broad range of energies well above of the excitation energy [16][17][18][19][20][21][22][23]. The enhanced absorption for transitions in resonance with the vHs at the tBLG leads to higher electron temperature (T e = 2900 K) at the tBLG and hence higher emission intensity than the SLG (T e = 2500 K).…”
Section: Resultsmentioning
confidence: 99%
“…Here we present studies that show photoluminescence (PL) emission from tBLG samples after femtosecond laser excitation showing a broad wavelength light emission. As in SLG the emission due to direct electron-hole recombination is not detectable [16][17][18][19][20][21][22][23] and the observed emission presents the black body thermal like behaviour. We show PL excitation (PLE) measurements by confocal scanning optical microscopy imaging to map the thermal emission intensity in the single layer and the bilayer regions in the samples.…”
Section: Introductionmentioning
confidence: 84%